Single‐platform, Attomolar Detection of Multiple Biomarkers by a Flexible SERS Sensor - Jaiswal, Ankita; Naqvi, Tania K.; Dwivedi, Prabhat K.; Verma, Sandeep (Chemistry, an Asian journal, 2023)
Early detection of Alzheimer's disease (AD) is critical for better healthcare management. Herein, we demonstrate a Surface Enhanced Raman Spectroscopy (SERS) active sensor for highly sensitive and selective detection of β‐Amyloid Peptide (Aβ1‐42), a biomarker of Alzheimer's disease. Polyacrylonitrile (PAN) nanofiber mats, containing purine‐based ligand (L; 0 mg (P1), 50 mg (P2), and 100 mg (P3)) were prepared by electrospinning followed by functionalization with silver nanoparticles (AgNPs). The fabricated SERS sensors were employed for the detection of Rhodamine 6G (Rh‐6G) dye for optimization and the highest sensitivity was achieved on P3/AgNPs SERS sensor. The P3/AgNPs sensor was chosen for the detection of Aβ1‐42 and human Insulin (HI). The limit of detection (LoD) was found to be 76×10−18M and 26×10−18M for Aβ1‐42 and HI, respectively. The sensitivity achieved is one order improved for Aβ1‐42 and four orders for HI when compared with reported values. Also, demonstrated the selectivity of the P3/AgNPs sensor by testing a simulated cerebrospinal fluid (CSF) and achieved easily identifiable peaks of Aβ1‐42 among the noise of HI and bovine serum albumin should be written before the acronym of BSA. This approach could be extended to develop ultra‐sensitive flexible SERS sensors for the facile detection of multiple biomarkers on a single platform with excellent sensitivity, selectivity and stability. A highly sensitive and selective flexible SERS sensor has been developed for detection of β‐ Amyloid Peptide (Aβ1‐42), a biomarker of Alzheimer's disease.